Experiential serious-game design for development of knowledge of object-oriented programming and computational thinking skills. Issue 4 (2nd October 2022) - Akkaya, Ali; Akpinar, Yavuz
ABSTRACT: Background and Context: Though still a nascent area of research, serious games have been presented as means of engaging students in computer programming and computational thinking due to their immersive and interactive nature. Existing research is limited in its ability to provide systems based on sound instructional design models, and only a few studies validate their design with statistical support. Objective: This study investigated the effects of a game which is based on experiential learning theory under framework of the four-component instructional design model on undergraduate students' learning performance in conceptual knowledge of object-oriented programming and computational thinking skills. Method: A pre-test and post-test quasi-experimental design was used to study the effects of the experiential serious games on conceptual knowledge of OOP and CT skills of 61 non-engineering students with and without prior programming knowledge. Findings: The statistical analyses reveal that students with and without programming experience significantly improved their understanding of fundamental concepts of OOP. There were only weak correlations among students' creative problem solving, attitudes towards digital game-based learning of programming, and learning. Implications: We provide several recommendations for researchers and practitioners for designing and developing an effective serious game to teach novice programmers computer programming.